Integrated energy system scheduling optimization considering vertical-axis wind turbines and thermal inertia in oilfield management areas - Wang, Xusheng; Cui, Jian; Ren, Bingpeng; Liu, Yanfeng; Huang, Yanfei (Frontiers in Energy Research, 2024)
Traditional horizontal axis wind turbines (HAWT) have limited efficiency in low wind speed regions. In this paper, an integrated energy system (IES) incorporating vertical axis wind turbines (VAWT) is proposed, this IES is located in an oil field management area, which can utilize the low wind speed resources more efficiently and improve renewable energy consumption, and also introduces a demand response model based on thermal inertia (TI) thus smoothing out the volatility brought by the VAWT. Typical output scenarios are obtained through stochastic optimization to deal with wind turbine and photovoltaic output uncertainties, and an optimal scheduling model is proposed to minimize the system operating cost. Finally, a simulation study was conducted in a micro-oilfield management area in Shandong Province, China, to demonstrate the performance of the proposed system. The results show that the IES using VAWT and TI can increase the renewable energy consumption capacity by 87% over the conventional HAWT system, change the user behavior, increase the economic efficiency by 12%, and achieve the smoothing of load-side fluctuation of electric and thermal loads, peak shaving and valley filling. This paper provides a feasible solution for an IES in low wind-speed areas.Nomenclature ESC